2008
DOI: 10.1159/000132401
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Women’s Cognitive Concept concerning Their Unborn prior to Prenatal Diagnosis

Abstract: Objective: We examined pregnant women’s expectations concerning their unborn babies prior to prenatal diagnosis and also the possible correlations with emotional characteristics such as anxiety and depression. Methods: The consecutive sampling consisted of 324 pregnant women presenting themselves between the 11th and 29th weeks of pregnancy for detection of foetal anomalies. The pregnant women noted their thoughts and expectations concerning their unborn using a choice of 18 adjectives in a 5-point Likert scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However the BAI gives no indication of a woman's underlying 'trait' anxiety. Kowalcek et al found that women who had an increased trait anxiety score were more likely to have an increased state anxiety score after an invasive test [47]. The recently developed Beck Anxiety Inventory-Trait (BAIT) may be a useful survey instrument for future research [48].…”
Section: Discussionmentioning
confidence: 99%
“…However the BAI gives no indication of a woman's underlying 'trait' anxiety. Kowalcek et al found that women who had an increased trait anxiety score were more likely to have an increased state anxiety score after an invasive test [47]. The recently developed Beck Anxiety Inventory-Trait (BAIT) may be a useful survey instrument for future research [48].…”
Section: Discussionmentioning
confidence: 99%
“…For that the prenatal period is a good chance for evaluating maternal-fetal attachment. (Atashi et al, 2018) Pregnancy is considered a vital and critical period in life as all of the pregnant mothers' behaviors, actions and thoughts could have more permanent effects on their fetuses than any other period of child's life (Kowalcek & Gembruch 2008) Moreover it is the period of development, therefore it is necessary to evaluate mother's attachment to her fetus more accurately. For that studying attachment during pregnancy would provide us a chance to learn more about this process, and studying this issue would help us understand and cope with the psychological problems during and after pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…A simples suspeita de uma malformação no feto ocasiona uma tensão psicológica para a mulher grávida e a ansiedade costuma acompanhar o período de diagnóstico (Kowalcek, 2007;Kowalcek & Gembruch, 2008;Kowalcek et al, 2003;Kowalcek, Mühlhoff, Bachmann, & Gembruch, 2002;Sahin & Gungor, 2008). O diagnóstico de uma malformação fetal desperta uma vivência psicológica de desilusão e descrença que suscita nos pais a o processo de luto pelo filho ideal (Caron & Maltz, 1994).…”
Section: Introductionunclassified